Bacterial toxin modulation of the eukaryotic cell cycle: are all cytolethal distending toxins created equally? - Gargi, Amandeep; Reno, Michael; Blanke, Steven R. (Frontiers in Cellular and Infection Microbiology, 2012)
The cytolethal distending toxins (CDTs) comprise a family of intracellular-acting bacterial protein toxins whose actions upon eukaryotic cells result in several consequences, the most characteristic of which is the induction of G2/M cell cycle arrest. Most CDTs are hetero-tripartite assemblies of CdtA, CdtB, and CdtC, with CdtB required for CDT-mediated cell cycle arrest. Several lines of evidence indicate that CdtA and CdtC are required for the optimal intracellular activity of CdtB, although the exact functional roles of CdtA and CdtC remain poorly understood. The genes encoding the CDTs have been identified in a diverse array of Gram-negative pathogenic bacteria. More recently, the genes encoding several CdtB subunits have been associated with alternatively linked subunits resembling the B-subunits of pertussis toxin. Although the CDTs are generally considered to all function as bacterial genotoxins, the extent to which individual members of the CDTs employ similar mechanisms of cell surface binding, uptake, and trafficking within sensitive cells is poorly understood. Recently, data have begun to emerge suggesting differences in the molecular basis by which individual CDTs interact with and enter host cells, suggesting the possibility that CDTs possess properties reflecting the specific niches idiosyncratic to those CDT bacterial pathogens that produce them. The extent to which functional differences between individual CDTs reflect the specific requirements for intoxicating cells and tissues within the diverse range of host microenvironments colonized by CDT-producing pathogenic bacteria remains to be experimentally explored.